Immunosenescence: Aging and Immune System Decline - Priyanka Goyani; Rafail Christodoulou; Evros Vassiliou (Vaccines)
Immunosenescence, a systematic reduction in the immune system connected with age, profoundly affects the health and well-being of elderly individuals. This review outlines the hallmark features of immunosenescence, including thymic involution, inflammaging, cellular metabolic adaptations, and hematopoietic changes, and their impact on immune cells such as macrophages, neutrophils, T cells, dendritic cells, B cells, and natural killer (NK) cells. Thymic involution impairs the immune system’s capacity to react to novel antigens by reducing thymopoiesis and shifting toward memory T cells. Inflammaging, characterized by chronic systemic inflammation, further impairs immune function. Cellular metabolic adaptations and hematopoietic changes alter immune cell function, contributing to a diminished immune response. Developing ways to reduce immunosenescence and enhance immunological function in the elderly population requires an understanding of these mechanisms.